Zonation Systems, School Culture And Education Quality: Effects On Student Motivation And Achievement - Rini Werdiningsih; Wahyu Wirasati; Slamet Riyono; Nursalim Nursalim (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
The contemporary state of Indonesian education grapples with challenges concerning educational quality. The zoning system stands as one policy initiative by the Ministry of Education and Culture (Kemendikbud) to ensure equitable access to educational services and an even dissemination of national education quality. This study aims to elucidate the impact of school zoning system policies and school culture on education quality, moderated through student motivation and achievement at Public schoolin Semarang City. A quantitative research approach was employed, involving 192 participants chosen through purposive sampling. Structural Equation Modeling (SEM) was employed as the data analysis method. Findings of this study reveal that both the school zoning system and school culture exhibit a significant, positive influence on student motivation and academic achievement. Consequently, these factors culminate in the enhancement of education quality within public senior high schools located in Semarang City. In sum, the study underscores the critical role of the zoning system and school culture in shaping student motivation, achievement, and, subsequently, the overall quality of education within the realm of public senior high schools.